Prediction of favourable sites for spin labelling of proteins. Issue 6 (2010) - Polyhach Polyhach, Yevhen Yevhen; Jeschke Jeschke, Gunnar Gunnar
Abstract : Electron paramagnetic resonance studies on diamagnetic proteins are based on site-directed spin labelling and require relatively much effort for engineering cystein point mutations as well as expressing and labelling the protein. Therefore, it is advantageous to predict those sites and pairs of sites that can provide the most precise and most reliable information on accessibility and distances. Systematic site scans based on a rotamer library approach for spin label side groups allow for such predictions. Figures of merit are defined that can be used to rank sites according to their potential suitability in studies of structure and structural changes. Such site scans can still provide useful results if only a backbone model and the amino acid sequence of the protein are known.